Effect of antimalarial chloroquine on the biodistribution of sodium pertecnetate in swiss mice - Barbosa, Vanessa Santos de Arruda; Lisboa, Marcelo José Santiago; Sampaio, Tarciso Bruno Montenegro; Lima, Hilkéa Carla de Sousa Medeiros; Holanda, Cecília Maria de Carvalho Xavier; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2015)
Background/Objective: Chloroquine is the prototype anti malarial drug, most widely used to treat all types of malaria except for disease caused by chloroquine resistant Plasmodium falciparum. It is also indicated in the treatment of rheumatoid arthritis, lupus erythematosus, giardiasis, amoebic and autoimmune hepatitis. Technetium-99m (99mTc) in the form of sodium pertechnetate (Na99mTcO4) is a radionuclide that connects to wide variety of molecules and cells. This study aimed to evaluate in vivo the influence of chloroquine on the biodistribution of Na99mTcO4- and histological pattern of Swiss mice. Methods: We used 14 male Swiss mice: treated group (n = 7) received chloroquine solution and control groups (n=7) received filtered water, for 15 days. Both groups received 0.1 mL (0.66 MBq) of Na99mTcO4- and the percentage of radioactivity per gram of tissue (%ATI/g) was determined. Parts of tissue samples were isolated for histologycal analysis. Results: Statistically significant difference in biodistribution of sodium pertechnetate (ATI%/g) was observed in blood and liver with increased radiotracer uptake in the treated group. Significant histological changes were seen in mesangial cells in the kidney and significant vascular congestion of the treated group. Conclusion: We conclude that the use of chloroquine in swiss mice interferes with the uptake of sodium pertechnetate in some organs and histological changes were visualized probably due to the presence of chloroquine toxicity.